Magnetoelectric oxide films for spin manipulation in graphene. Issue 3 (29th January 2016) - Stuart, S. C.; Gray, B.; Nevola, D.; Su, L.; Sachet, E.; Ulrich, M.; Dougherty, D. B.
Abstract : The challenge of creating a graphene spin field effect transistor (spin‐FET) demands a magnetic gate dielectric material whose magnetization can be switched electrically. We have grown films of Cr2 O3 on top of graphite and graphene by pulsed laser deposition that shows this crucial functionality. We demonstrate that the Cr2 O3 films are magnetoelectric by poling them in combined electric and magnetic fields and then using magnetic force microscopy to observe spontaneous surface domain structure as a function of poling field. In addition, we show that the electric field created by a conducting AFM tip can be used to write magnetic patterns in the film that demonstrate the kind of continuous magnetoelectric control needed for a prototype spin‐FET. (© 2016 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : Magnetoelectric ordering (red vs. blue contrast) at the surface of Cr2 O3 films on graphite and graphene substrates is observed by magnetic force microscopy. In addition, local electrostatic fields applied with an AFM tip can control the surface ordering, a prerequisite for finally realizing a graphene spin field effect transistor.